How does economic growth impacted by economic freedom? A case study of the Middle East Region - Saeed, Mohammed Ahmed; Shaiekh, Lama Tariq (Asian Journal of Economic Modelling, 2025)
The study aimed to analyze the impact of economic freedom on economic growth and foreign direct investments concerning a country's political stability. The research employed a correlation design. It focused on 11 Middle Eastern countries over a period of 22 years. The study used the Autoregressive Distributed Lag (ARDL) method to estimate short- and long-term relationships. Results demonstrated that economic freedom significantly and positively affects economic growth in the long run, while civil liberties positively influence both economic growth and foreign direct investment in both the short and long term. Conversely, the study found that political rights have a negative impact on long-term growth, suggesting that in the Middle East, democratic expansion is associated with policy uncertainties that hinder growth. Additionally, the findings indicated that foreign direct investment in the Middle East is driven by civil liberties rather than political stability or economic freedom, highlighting the importance of institutional transparency. Overall, the findings emphasize the significance of institutional quality as a key driver of sustained economic performance in the region. Therefore, Middle Eastern governments should implement structural reforms to safeguard trade and economic freedoms.